Investigating the effects of streaming the grade 6 pupils according to their ability at Dumezweni Primary School in Khami District. - Moyo, Jane (Midlands State University, 2020)
This document presents the findings on the perceptions of pupils and teachers of Dumezweni Primary school on the effects of the streaming of the grade 6pupils according to their ability at Dumezweni Primary School in Khami District. The study used a combination of the qualitative and quantitative research approach. A descriptive and explanatory research design was used in this study because people sometimes fail to understand raw data. So the descriptive and the explanatory research design makes raw data understandable in this research. A sample of eighteen grade six pupils and seven grade six teachers was used. Judgemental sampling was used to select the pupils for this study; the researcher relied on her experience as a classroom practitioner to select the pupils who had a record of performing well, the mediocres and those who performed badly in class. As for the teachers, the researcher used convenience sampling whereby the researcher selected subjects who were easily accessible and willing to participate in the study. Data is presented in the form of tables and bar graphs and different scores are interpreted using the Likert scale. The research findings were that the majority of teachers and pupils at Dumezweni Primary who were sampled for this study were in favour of the streaming of pupils according to their ability. They cited some very pertinent and valid reasons for that. The major reason they cited was that the streaming of pupils according to their ability was very beneficial to both the slow learners and the gifted learners. Those who were against streaming cited the fact that streaming dehumanises pupils, it causes stigmatisation and labelling of the slow learners. vi The study strongly recommends that streaming should be adopted in schools since it has got some notable benefits. The problem of the dehumanisation of the slow learner through labelling should be thoroughly dealt with by the teachers and the heads of schools since they are the ones who are responsible for setting the tone of the school. The pupils and the parents must also be enlightened on the benefits of streaming pupils according to their ability. If streaming is done properly the problem cited above will be a thing of the past.